Pengaruh Motivasi Belajar Siswa Pembelajaran Fisika SMAN 3 Kota Sungai Penuh Kelas XI MIPA - Tinur Hasibuan (Integrated Science Education Journal, 2022)
Research Objectives: The purpose of this study was to determine the physics learning ability of students in class XI MIPA SMAN 3 Sungai Penuh, and to motivate students to learn physics. Methodology: This study uses a quantitative research type with the research subjects of class XI MIPA students of SMAN 3 Sungai Penuh. The data collection instrument was in the form of a student learning motivation questionnaire using google from. Data analysis uses descriptive statistics with the aim of describing the object of research or research results Main findings: The results showed that basically physics learning at SMAN 3 Sungai Penuh is in class XI MIPA. Because in learning physics students have less interest in learning so that it does not encourage student learning motivation, students will have difficulty in studying physics and cannot connect with concepts. To encourage student motivation, what the teacher must do is ensure students can master the material. Novelty of the study: After conducting the research, it was found that the novelty of this research is the influence between motivation and student learning outcomes in learning physics at SMAN 3 Sungai Penuh.